U.S. history: American stories - Hiebert, Fredrik T.; Altoff, Peggy; Fischer, Fritz; Garrett, Ken; Kelly, John; Kelso, William M.; Reid, Robert; Sabeti, Pardis; Slater, Donald (National Geographic Learning/Cengage, 2018)
"US History: American Stories, Beginnings to 1877 is a middle school U.S. History program that matches content rigor and richness with accessibility for all students. The program connects historical events to students’ lives today and promotes empathy, tolerance, and understanding for all people. Emphasis is on student engagement, empowerment, and active citizenship. True to National Geographic’s mission, American Stories embraces diversity, honors cultural heritage, and advocates for taking care of the planet we all share. History is the story of people. It is a living thing, and students are part of it. American Stories encourages students to become stewards of the past—the protagonists of their own discoveries."--From publisher's website